A-2: COMPENSATION FOR DELAY DAMAGES IN THE LEGAL SYSTEMS OF AFGHANISTAN AND IRAN AND ISLAMIC JURISPRUDENCE: تعویض أضرار تأخير الدفع في النظام القانوني لأفغانستان وإيران والفقه - Mutawakel, Mohammad Yasin; Ata, Rafiullah (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2023)
Entering into a contract brings about consequences, and both parties are obligated to abide by its terms and implications. If either party fails to adhere to the contract’s provisions or refuses to fulfill their obligations, the other party has the right to take necessary measures to seek compensation for the breach of the contract, either directly or through the judicial system. The concept of "delay damages" refers to the financial loss that the debtor incurs due to the delay in repaying a debt. Legislators and legal scholars have emphasized the issue of compensation for delay in payment to ensure that debtors fulfill their obligations by repaying their debts within the specified or pre-agreed timeframe. In case of failure to pay within the mentioned timeframe, in addition to repaying the principal debt, the debtor is also required to compensate for the damages resulting from the delay in payment. Some argue that the nature and standards for calculating delay damages are related to currency devaluation, while others attribute it to the loss of benefit. Some view it as a contractual civil liability. It is important to note that the damages that can be claimed and paid due to delay in payment are not additional compensations on top of the debt; rather, they represent a separate obligation arising from the debtor’s negligence.